2018
DOI: 10.1097/inf.0000000000001910
|View full text |Cite
|
Sign up to set email alerts
|

Moxifloxacin in Pediatric Patients With Complicated Intra-abdominal Infections

Abstract: MXF treatment was well tolerated in children with cIAIs. However, a lower clinical cure rate was observed with MXF treatment compared with COMP. This study does not support a recommendation of MXF for children with cIAIs when alternative more efficacious antibiotics with better safety profile are available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 30 publications
2
35
0
Order By: Relevance
“…Based on the known pharmacological profile of moxifloxacin and a therapeutic target range established in adults, an age‐dependent dosing scheme for moxifloxacin could be proposed (learning step) and tested in the first‐in‐children trial . The analysis of the uncertainties associated with model‐based predictions using phase I results as a reference resulted in refined doses that were confirmed in the larger phase III study investigating moxifloxacin treatment for cIAIs in children . After the completion of both trials, a pediatric popPK model for moxifloxacin was developed, and the resulting PK parameters were compared with the initial PBPK predictions to (i) retrospectively evaluate the PBPK model predictability, (ii) confirm the proposed dosing schedule of moxifloxacin in children, and (iii) support PK‐related clinical safety/efficacy questions (confirmation step).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the known pharmacological profile of moxifloxacin and a therapeutic target range established in adults, an age‐dependent dosing scheme for moxifloxacin could be proposed (learning step) and tested in the first‐in‐children trial . The analysis of the uncertainties associated with model‐based predictions using phase I results as a reference resulted in refined doses that were confirmed in the larger phase III study investigating moxifloxacin treatment for cIAIs in children . After the completion of both trials, a pediatric popPK model for moxifloxacin was developed, and the resulting PK parameters were compared with the initial PBPK predictions to (i) retrospectively evaluate the PBPK model predictability, (ii) confirm the proposed dosing schedule of moxifloxacin in children, and (iii) support PK‐related clinical safety/efficacy questions (confirmation step).…”
Section: Discussionmentioning
confidence: 99%
“…During conduction of the phase I and III studies, these dose recommendations were subject to clinical validation and assessment through independent safety boards, allowing for the adjustment of the recommended doses if deemed necessary. The details of the clinical dose adjustment steps are presented in the clinical papers describing the phase I and III trials of moxifloxacin in children …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure shows the single‐dose exposure (expressed as area under the concentration‐time curve [AUC]) predicted for children with a PBPK model in comparison to the data observed in the first clinical trial with rivaroxaban in children . Another example is the fluoroquinolone antibiotic moxifloxacin the clearance of which was predicted in children by PBPK modeling before the conduction of pediatric trials and compared with individual data observed in 2 pediatric trials . In both case examples, PBPK modeling in children using previous ontogeny information has been proven to be very helpful to guide the development of suitable dosing regimens in pediatric development programs.…”
Section: Application Of Pbpk In Pediatric Researchmentioning
confidence: 99%